RESEARCH ON FATIGUE CRACK PROPAGATION OF LEAF SPRING UNDER VARIABLE AMPLITUDE LOAD - XIANG YuXia; WU ZhiFei (Jixie qiangdu)
The prediction model of leaf springs fatigue crack growth under variable amplitude loads is mainly Schütz phenomenological model. However, the effect of the crack closure effect on fatigue crack propagation and the relationship between the parameters and the stress ratio wasn’t considered. The threshold value of the fatigue crack was only suitable for the special working conditions where the stress ratio is 0. Therefore, the Schütz fatigue crack propagation phenomenological model was improved, which caused the physical parameters meaning more accurate, suitable for different working conditions. The stress measured by the actual vehicle test was applied to the modified model to describe the progress of leaf spring fatigue crack growth under the variable amplitude load. The results show that the crack growth rate increases with the loading amplitude. The test results are in good agreement with the model prediction results, which provides a theoretical basis for the calculation of fatigue crack growth rate under variable amplitude load.